The Locating Chromatic Number of Pentagonal Circular Ladder Graph PCLn - Des Welyyanti; Annisa Wahyuni; Haripamyu (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2025)
Locating coloring is a type of vertex coloring applied to connected graphs, where each vertex is assigned a color such that adjacent vertices receive different colors. In this setting, each color corresponds to a color class, which consists of all vertices assigned that color. A central notion in locating coloring is the color code of a vertex, determined by its distances to each color class. A coloring is classified as a locating coloring when every vertex in the graph has a unique color code. The locating chromatic number of a graph is the minimum number of colors needed to achieve such a coloring. The Pentagonal Circular Ladder graph is a structure formed by combining a circular graph with pentagonal components. This article examines the locating chromatic number of the Pentagonal Circular Ladder graph and provides an analysis of the behavior of locating colorings within this graph family.Keywords: Locating chromatic number; Partition; Locating coloring; Color code; Pentagonal Circular Ladder Graph. AbstrakPewarnaan lokasi merupakan jenis pewarnaan titik yang diterapkan pada graf terhubung, di mana setiap titik diberi warna sehingga titik-titik yang bertetangga tidak memiliki warna yang sama. Dalam konteks ini, setiap warna membentuk sebuah kelas warna yang terdiri atas seluruh titik yang diberi warna tersebut. Salah satu konsep utama dalam pewarnaan lokasi adalah kode warna suatu titik, yang ditentukan berdasarkan jaraknya terhadap setiap kelas warna. Suatu pewarnaan disebut pewarnaan lokasi apabila setiap titik dalam graf memiliki kode warna yang berbeda. Bilangan kromatik lokasi dari suatu graf didefinisikan sebagai jumlah minimum warna yang diperlukan untuk menghasilkan pewarnaan semacam ini. Graf Pentagonal Circular Ladder merupakan struktur graf yang dibentuk melalui penggabungan graf lingkaran dengan komponen-komponen pentagonal. Artikel ini mengkaji bilangan kromatik lokasi dari graf Pentagonal Circular Ladder serta memberikan analisis mengenai perilaku pewarnaan lokasi pada keluarga graf tersebut.Kata Kunci: Bilangan kromatik lokasi; Partisi; Pewarnaan lokasi; Kode warna; Graf Pentagonal Circular Ladder. 2020MSC: 05C12, 05C15.